Analisis Ukuran Jendela Hotel untuk Meminimalisir Pengunaan Energi Pada Bangunan - Muhammad Fadly Saleh (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2017)
The use of fossil fuel becomes one of the cause of global warming. Buildings are massive energy users. This research aims to analyze the size of hotel windows to minimize energy use on buildings. This research is a quantitative research, using observation and experimental methods. The research object is the Four Points Hotel building, located in Jln. Landak Baru of Makassar City. Observation of the building’s physique is conducted on the building plans and the conditions of the building’s project location. The experiment of the observation results by analyzing some windows sizes using an energy simulation computer program called eQuest. After resizing the windows of Four Points Makassar building, the building energy consumption on the typical floor decreased up to 9.59% from the energy consumption of the existing building. The window size used is 10% of the exterior wall area